Early‐stage comparative effectiveness: Randomized controlled trial with histamine inverse agonist MK‐7288 in excessive daytime sleepiness patients. (4th October 2013) - Sun, Hong; MacLeod, Catherine; Mostoller, Kate; Mahon, Chantal; Han, Lingling; Renger, John J.; Ma, Junshui; Brown, Kevin R.; Schulz, Valerie; Kay, Gary G.; Herring, W. Joseph; Lines, Christopher; et al.
Abstract Histaminergic neurons are regulators of the sleep–wake cycle. We evaluated the alerting effects of MK‐7288 (10, 20 mg), a novel histamine‐3 receptor inverse agonist (H3RIA), along with modafinil (200 mg), a standard treatment, in a randomized, double‐blind, placebo controlled, crossover study of 56 patients with excessive daytime sleepiness (EDS). Efficacy was assessed using maintenance of wakefulness tests (MWT) and car driving simulation tests. MK‐7288 and modafinil significantly prolonged MWT sleep latency (improvements vs. placebo of 8.1 to 8.2 min for MK‐7288 and 10.2 min for modafinil), and improved car driving simulation standard deviation of lane position (reduction vs. placebo of −0.1 m for each treatment). MK‐7288 was associated with more insomnia (29%) than modafinil (9%) and placebo (6%). The study demonstrated the potential of the H3RIA mechanism for treating EDS, but did not show efficacy differentiation from modafinil. Early‐stage comparative effectiveness can help prevent late‐stage failure and increase the cost‐effectiveness of drug development.